Inventory Management and Warehousing of Dhaka Water Supply and Sewerage Authority (DWASA) - Nazir, Md Shahid (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2020..